2020
DOI: 10.2147/cmar.s260147
|View full text |Cite
|
Sign up to set email alerts
|

<p>Onco-Metabolic Surgery: A Combined Approach to Gastric Cancer and Hypertension</p>

Abstract: The purpose of this study was to explore the changes in blood pressure in patients with concurrent gastric cancer and hypertension after gastrectomy, and to identify the factors that affect the changes in blood pressure. Materials and Methods: Patients with concurrent gastric cancer and hypertension who underwent gastrectomy were retrospectively analyzed from January 2013 to December 2018. The pre-and 6-month postoperative medical records were compared. Predictors for the remission of hypertension were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…In bariatric surgery, patients had T2DM improvement and apparently lower microvascular and macrovascular disease and mortality after surgery (23). Similarly, patients had remission of T2DM and hypertension after gastric cancer surgery (14,24), and onco-metabolic surgery occurred. There were some reasons and theories accounting for the remission of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In bariatric surgery, patients had T2DM improvement and apparently lower microvascular and macrovascular disease and mortality after surgery (23). Similarly, patients had remission of T2DM and hypertension after gastric cancer surgery (14,24), and onco-metabolic surgery occurred. There were some reasons and theories accounting for the remission of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…GC patients also experience hypertension remission after gastrectomy. Peng et al [ 15 ] conducted a retrospective study of 143 patients who underwent gastrectomy and the resulting effects on hypertension and found that the hypertension complete remission rate was 55.3%. In addition, age and total gastrectomy were predictors of hypertension remission 6 mo after gastrectomy[ 15 ].…”
Section: Hypertension Remissionmentioning
confidence: 99%
“…Peng et al [ 15 ] conducted a retrospective study of 143 patients who underwent gastrectomy and the resulting effects on hypertension and found that the hypertension complete remission rate was 55.3%. In addition, age and total gastrectomy were predictors of hypertension remission 6 mo after gastrectomy[ 15 ]. Wang et al [ 19 ] compared hypertension remission between total gastrectomy and subtotal gastrectomy in non-obese non-diabetic GC patients and found that total gastrectomy itself, beyond weight loss, was associated with hypertension remission[ 19 ].…”
Section: Hypertension Remissionmentioning
confidence: 99%
See 2 more Smart Citations